Dystrophic calciphylaxis in panniculitis: features of the clinical picture and diagnosis - O. N. Egorova; A. V. Datsina; M. V. Severinova (Современная ревматология)
The clinical presentation of lobular panniculitis (PN) associated with calciphylaxis (CP, calcification) can vary widely and may be associated with joint and internal organs involvement, making the diagnosis of the disease difficult.Objective: to evaluate the frequency and significance of CP in patients with PN using long-term prospective follow-up.Material and methods. From 2018 to 2023, at the V.A. Nasonova Research Institute of Rheumatology 217 patients with referral diagnosis "erythema nodosum" or "panniculitis" were examined. In 19.3% of cases (9 men and 33 women aged 37 to 72 years) CP was confirmed with an average disease duration of 56.3±11.2 months. Clinical examination of patients was performed according to the standards recommended by the Russian Association of Rheumatologists. International criteria were used to confirm the diagnosis of systemic lupus erythematosus (SLE), idiopathic inflammatory myopathies (IIM), systemic sclerosis (SS), and lipodermatosclerosis (LDS). In 12 patients with indurations, pathological examination of biopsy specimens of skin and subcutaneous fatty tissue from the area of induration was performed, which allowed confirming the diagnosis of idiopathic lobular PN (ILPN) in 3 cases. Four grades of calcification were distinguished according to the size and depth of the calcifications. In addition, considering the type of radiological changes and clinical manifestations, four subtypes of CP were identified: mousse-like, stone-like, mesh-like and lamellar-like.Results and discussion. In the study group, the ratio of women to men was 3.6:1, and the mean age was 43.8±7.6 years. On clinical examination we determined, in 60% of cases CP predominantly stone-like subtype (71.4%) of first grade (47.6%), which was significantly more frequently located on the upper and/or lower extremities and/or trunk (57.1%; p=0.05). Using clinical, laboratory and instrumental data, we confirmed the development of CP in ILPN (n=3), SLE (n=3), LDS (n=21), IIM (n=5), SS (n=1), and idiopathic CP (n=9) with a mean disease duration of 8.7±2.4 years.An increase in ESR and CRP levels occurred in different diseases, while urinary syndrome was associated with SLE (66.6%) and an increase in creatinine phosphokinase with IIM. Decreased calcium and 25-hydroxyvitamin D levels and increased phosphorus and parathyroid hormone levels were found in many patients studied.Conclusion. In the absence of clear diagnostic criteria for CP in patients with PN, early diagnosis is critical for the development of an effective multidisciplinary treatment plan.